The politics of burden-sharing in the refugee regime: The refugee as point of reference - van de Fliert, Mark (AUC Knowledge Fountain, 2018)
This thesis applies international relations theory to better understand the political maneuvering of states in refugee affairs. It argues that previous contributions to this debate have used a wrong paradigm to describe burden-sharing politics in the refugee regime, resulting in models which are too static to capture the high-politics of refugee affairs. In particular, the thesis criticizes the "North vs. South" model proposed by Betts (2009), which argues that the burden-sharing politics in the refugee regime can be understood as an opposition between states in the global "North" and global "South". Where Betts uses the geographic position of the state to understand burden-sharing politics in the refugee regime, the essay argues that it is in fact the geographic position of the refugee which matters. Replacing the state-centered paradigm with a refugee-centered paradigm, it then argues that state maneuvering in the refugee regime should not be described as a North vs. South impasse, but as a zero-sum game between states seeking to evade asylum-burdens and states seeking to reduce refugee-burdens.